PENINGKATAN PENDAPATAN PETANI MELALUI BUDIDAYA TANAMAN GAHARU (AQUILARIA MALACCENSIS) DI DESA URAUR KECAMATAN KAIRATU KABUPATEN SERAM BAGIAN BARAT - Matinahoru, Johan Markus (MAANU: Jurnal Pengabdian Kepada Masyarakat, 2023)
In general, farmers harvest agarwood by cutting down or destroying the trees. Therefore the effort that must be made is to invite the community to plant agarwood as an Artificial Forest. In connection with the availability of a lot of empty and abandoned critical land in Uraur Village, Kairatu District, West Seram Regency, it is necessary to conduct training on agarwood cultivation so that farmers can cultivate their vacant land with this type of agarwood plant. The purpose of this service is to increase the understanding and skills of agarwood cultivation. While the benefits to be achieved are farmers can cultivate agarwood plants as a substitute for income for the family. Participants were very responsive to this training, because it was something new for farmers. So far, farmers have focused more on cultivating cloves, nutmeg and cocoa but the results have always been suboptimal. In addition, from the aspect of understanding the training material, it was very good, because 90% of the participants were able to answer the evaluation questions well. It is hoped that the participants can immediately try cultivating agarwood plants because it is very promising to be able to increase farmers' income in the future when harvest time comes.